Correlation Between Postoperative Distribution of Lordosis and Reciprocal Progression of Thoracic Kyphosis and Occurrence of Proximal Junctional Kyphosis Following Surgery for Adult Spinal Deformity. Issue 9 (November 2018) - Ohba, Tetsuro; Ebata, Shigeto; Oba, Hiroki; Koyama, Kensuke; Haro, Hirotaka
Abstract : Study Design: This was a retrospective cohort study using consecutive patients. Objectives: The objectives of this study were to evaluate the effect of lumbar lordosis (LL) construction on postoperative reciprocal progression of thoracic kyphosis (TK) and occurrence of proximal junctional kyphosis (PJK) following surgery for adult spinal deformity (ASD). Summary of Background Data: A large postoperative TK has been reported as an iatrogenic risk factor for PJK following surgery for ASD. Therefore, knowing how to anticipate and regulate postoperative reciprocal progression in TK with LL restorative surgery is important to prevent PJK. The LL proportion including distribution of the lordosis (lordosis distribution index: LDI) in the lower (L4–S1) and upper (L1–L3) arcs has been known as important because it alters the distribution of load. However, the influence of postoperative LL construction on postoperative reciprocal change in TK resulting in PJK is largely unknown. Methods: Sixty-six consecutive patients with ASD treated with LL restorative surgery with a fusion level consistently selected from T8–T10 to the pelvis and followed-up for a minimum of 1 year. Abnormal PJK was evaluated according to the Boachie-Adjei classification. Roland-Morris Disability Questionnaire and Oswestry Disability Index were measured at 1 year after surgery. Results: The prevalence of PJK in the present study was 33.3%. Outcomes of patients with PJK were significantly worse than in patients without PJK, regardless of PJK grade. Postoperative reciprocal progression in TK with LL restorative surgery was found. Preoperative risk factors of PJK were older age and smaller sacral slope angle. Postoperative risk factors for PJK included increased TK and decreased LDI. We found a strong correlation between postoperative LDI and reciprocal progression of TK resulting in PJK. Conclusions: Postoperative LDI is crucial to prevent excess reciprocal progression of TK resulting in PJK.